2022
DOI: 10.1002/osp4.589
|View full text |Cite
|
Sign up to set email alerts
|

The use of very low‐calorie diets in subjects with obesity complicated with nonalcoholic fatty liver disease: A scoping review

Abstract: This scoping review synthesizes the existing research on the use of very low‐calorie diets (VLCDs) in subjects with nonalcoholic fatty liver disease (NAFLD) and end‐stage liver disease (ESLD). 19 studies were included, of which 5 were clinical trials, 11 were cohort studies, 1 was a case‐control study, and 2 were case series totaling 968 subjects. About 17 studies were focused on patients with NAFLD while the two case series described in patients with ESLD on the transplant list or post‐liver transplant. Six s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…There is extensive evidence detailing the relationship between WL and improvement of NAFLD and IR. [16][17][18][19][20] In the current study, significantly lower blood glucose levels were observed in the WL group, indicating a tendency toward better glycemic metabolism in this group. In addition, lower frequencies of macro-and microvesicular steatosis and portal inflammation were observed in the pre-operative WL group.…”
Section: Discussionsupporting
confidence: 48%
“…There is extensive evidence detailing the relationship between WL and improvement of NAFLD and IR. [16][17][18][19][20] In the current study, significantly lower blood glucose levels were observed in the WL group, indicating a tendency toward better glycemic metabolism in this group. In addition, lower frequencies of macro-and microvesicular steatosis and portal inflammation were observed in the pre-operative WL group.…”
Section: Discussionsupporting
confidence: 48%
“…A systematic review confirmed that VLCD led to a significant weight loss of 2.8 to − 14.8 kg together with liver size reduction (− 5–20% of the initial volume) [ 29 ]. A more recent study comparing the effect of VLCD, and LCD showed that VLCD was more effective in reducing total body weight [ 30 ]. VLCKD demonstrated similar VLCD weight loss results, but with a significant liver volume reduction (5.8 vs. 4.2%) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study comparing the effect of VLCD, and LCD showed that VLCD was more effective in reducing total body weight [ 30 ]. VLCKD demonstrated similar VLCD weight loss results, but with a significant liver volume reduction (5.8 vs. 4.2%) [ 30 ]. The efficacy of liraglutide on weight loss has been demonstrated by the Safety and Clinical Adiposity–Liraglutide Evidence (SCALE) trials.…”
Section: Discussionmentioning
confidence: 99%
“…VLCKD is known to ameliorate liver function, [44][45][46] reducing intrahepatic fat content, 47 and increasing the insulin sensitivity index. 48 In obese patients with T2DM, the reduction in carbohydrate intake has been associated with an early and significant decrease in hepatic triacylglycerol content.…”
Section: Discussionmentioning
confidence: 99%